Elite cross country skiers` zonetime adaptation markers applicable in pre-season with jet lags and acclimatization periods - Grushin, A. A.; Yashina, E. R.; Abramova, T. F. (Theory and Practice of Physical Culture, 2018)
The study analyzes benefits of the elite cross country skiers` zonetime adaptation markers applicable in pre-season with jet lags. The study analyzed the elite cross country skiers ` (n=19) daily physical debelopment tests; plus the body anthropometric characteristics; autonomous nervous and cardiovascular system functionality tests; and biochemical adaptation markers. The study made it possible to find the highly informative zonetime adaptation markers including pulse pressure; orthostasic blood pressure; free testosterone and cortisol and their ratios; total albumen, urea, magnesium, AST activity, glucose and insulin rates; plus self-rated determination for training. In case of the elite cross country skiers, the list may also include muscular mass, creatinine and calcium rates. The completion stage of the pre-season with a jet lag is recommended to be finalized with the prior acclimatization period taking 7-9 days. The acclimatization completion terms and adaptation markers reactivity rates are largely dependent on the sport discipline, background wellbeing and fitness rates; prime acclimatization and pre-season training design and management quality, intensity of competitive period; and total terms of prior acclimatization stage